The face on the milk carton - Cooney, Caroline B. (New York : Bantam Doubleday Books for Young Readers, 1994)
A photograph of a missing girl on a milk carton leads Janie on a search for her real identity.
Child Study Children's Book Committee.
School Library Journal.
Wilson's Junior High School.
6.9
5-8
Keywords: Kidnapping -- Fiction; Missing children -- Fiction; Kidnapping -- Fiction; Missing children -- Fiction